Evaluation of the role of cultural-religious indices in tourism development with an emphasis on the Chehel Dokhtar ritual in Khorram Abad city - ali amiri; mandana masoudi rad; somayeh bakhshizadeh; hosein zaree (تحقیقات کاربردی علوم جغرافیایی)
Religious tourism, as one of the ways of development, cultural exchange and social interaction between nations can have many benefits for any society today. Enjoying indigenous cultures and local religious ethics is an important factor in attracting tourists. The city of Khorramabad has special religious ethics, such as the celebration of gellmalli in the Ashura Day and the chehell manbarr in Tasoa day, which can have a profound effect on this. Therefore, the present article, using descriptive-analytical method, and questionnaire, interview and observation tools, and with the assumption that indigenous religious-cultural ethics increase the value and importance of tourist attractions at the destination, has attempted to survey the role of chehell manbarr in tourism development of  Khorramabad city. The results of one sample T-test at the significant level of 0.000 indicate the impact of all three indicators of abilities and potentials in the chehell manbarr, visual beauties and custodians of urban organizations such as Culture and Islamic Guidance, Municipalities and other related organizations Is above average; Also according to the results of one-way analysis of variance at the error level below 0.05% , it is vary the effect of the index of abilities and potentials in the chehell manbarr ceremonies, and the effect of metropolitan organizations such as culture and Islamic guidance and municipality according to the educational levels of the respondents. However, the results of one-way analysis of variance for the extent of visual beauties on tourism inclination are similar at the educational level of the respondents. The results of regression analysis at the significant level of 99% show that all three variables of keeping of urban organizations such as culture and Islamic guidance during the chehell manbarr ceremonies, the abilities and potentials in the chehell manbarr ceremonies and the creation of visual beauties have a direct and significant effect on the tendency to Tourism and motivation for future trips.